Treatment Strategies in Acute Post-operative Endophthalmitis after Cataract Surgery at a Tertiary Eye Hospital in Nepal: A 5-year Retrospective Review - Suwal, Barsha; Khadka, Deepak; Shrestha, Arjun; Shrestha, Rajan (Nepalese Journal of Ophthalmology, 2021)
Introduction: Despite best possible preventive measures, acute postoperative endophthalmitis (POE) is still the most devastating, sight-threatening complication after intraocular surgery and the most feared complication by treating surgeons. Materials and methods: It is a retrospective study of 22 eyes diagnosed as acute POE following cataract surgery in the last 5 years (2015-2019), aimed to evaluate the treatment strategies used in its management. Main outcome measures evaluated were rates of repeat intravitreal injection, adjunctive therapeutic regimens, pars plana vitrectomy (PPV) and visual outcome. Results: Twenty one eyes (95.45%) received repeated intravitreal injection. Adjuvant intravitreal steroid was used in 12 eyes (54.54%), oral steroid in 16 eyes (72.72%) and oral antibiotic in 8 eyes (36.36%). PPV was done in 8 eyes (34.78%) and all 8 eyes that underwent PPV had a vision of Hand Movement (HM) close to face. 7 eyes (87.5%) had early PPV within 1 week of diagnosis. The median best corrected visual acuity (BCVA) improved from 1.00 logMar to 0.8 logMar following treatment at 3 months follow up (p= 0.117). Conclusion: Repeat intravitreal injections were commonly employed. Early PPV was performed more commonly regardless of the visual acuity at the time of diagnosis of acute POE.